Geotechnical and Abutment Stability Analysis for the Replacement of Way Merah 2 Bridge - Affandi; Yoga Marta Agustiawan; Sari Utama Dewi (Universitas Medan Area, 2026)
The Way Merah 2 Bridge, located on the Gedong Aji Baru–Rawajitu road section in Lampung Province, has experienced structural deterioration and insufficient capacity, necessitating bridge replacement to ensure transportation safety and serviceability. This study aims to evaluate the geotechnical characteristics of the foundation soil, determine the axial bearing capacity of pile foundations, and assess the structural stability of the bridge abutment under various loading conditions. The research employed a quantitative analytical approach using field investigation data, including borehole, Standard Penetration Test (N-SPT), and cone penetration test results, combined with numerical modelling using MIDAS Civil software. Geotechnical analyses were conducted to determine soil classification, pile bearing capacity, deformation behaviour, and abutment stability against overturning and sliding under service, extreme, and seismic load combinations based on Indonesian bridge design standards. The results indicate that the study area is classified as Site Class SD (medium soil) with an average N-SPT value of 18.65. The allowable axial pile capacity of 839.20 kN exceeds the maximum applied axial load of 580.64 kN, indicating adequate foundation performance. Structural deformation remained within allowable limits, while most loading combinations satisfied the required safety factors, except one extreme overturning condition. These findings demonstrate that the proposed bridge replacement design is structurally and geotechnically feasible and provide practical guidance for improving bridge abutment performance under extreme loading conditions.